PERAN STRATEGIS PENDIDIKAN DAN KESEHATAN DALAM MENDORONG PERTUMBUHAN EKONOMI YANG INKLUSIF DAN BERKELANJUTAN - Agus Baskara (Educatus, 2025)
Education and health are two main components in human resource development that have a significant impact on a country's economic growth. This study aims to examine how the quality and access to education and health services directly and indirectly affect the economic development process. Quality education improves the skills, productivity, and innovation of the workforce, while good health allows individuals to work optimally and actively participate in economic activities. The results of the study show that investment in education and health not only accelerates economic growth but also encourages the creation of inclusive, sustainable, and equitable development. Therefore, national development policies need to pay special attention to improving the quality and equality of access to education and health services as a primary strategy in strengthening the foundation of the long-term economy.